Collaborative Governance In Planning Tourism Arrangement Towards World Tourism In BAPPEDA Pangandaran District - Ahmadi, Rulan (Decision, 2022)
This research aims to determine Collaborative Governance in Planning Tourism Management towards World Tourism in Bappeda Pangandaran Regency. This research uses descriptive research methods with a qualitative approach. Where the type of data consists of primary data obtained through interviews, direct observation and documentation in the field, while secondary data is obtained from data that researchers have collected through documents related to the research. The analysis techniques in this research are data reduction (Data Reduction), data presentation (Data Display), and drawing conclusions (Conclusion Drawing). The research results show that the Collaborative Governance process in Tourism Management Planning towards World Tourism in the Pangandaran Regency Bappeda has been running since Pangandaran began to separate itself from Ciamis. Based on the research results, it can be concluded that the Collaborative Governance process in planning Tourism Arrangement in Pangandaran Regency has been organized and also invites the community to contribute to the development of tourism in Pangandaran Regency.